Operations Strategy - Slack, Nigel (Pearson International Content, 2023)
"Sets the standard for excellence in the field and distinguishes itself as a truly vital and comprehensive book within its domain. The book is enriched by numerous real-world and up-to-date examples, along with insightful case studies, ensuring that the readers gain a holistic understanding of the subject." Dr Arijit Bhattacharya, Associate Professor in Operations & Supply Chain Management, Norwich Business School, UEA The go-to resource on operations strategy, exploring key activities, processes and decisions adopted by a wide range of businesses Operations Strategy, 7th edition encourages a thorough understanding of the topic, building on concepts from strategic and operations management to marketing and HR management. The way an organisation manages their operations strategically can have a huge impact on its prospects – whether large or small, service or manufacturing, for-profit or not-for-profit, international or local. Operations strategy is fundamental to the success of any organisation and a major source of competitive advantage. The text encourages you to explore the key strategic decisions adopted by a wide range of organisations in different sectors, and is ideal for MBA students, upper-level undergraduates, postgraduates and executives. "Slack and Lewis have approached the ethical, societal, and environmental issues affecting business operations strategy in a post-pandemic world, with a blend of new chapters and contemporary case studies based on both external and internal contexts – an essential item for any serious Operations Strategy resource list." Jamie Rundle, Senior Lecturer in Management, Nottingham Business School, UK New to this edition: More on responsible and sustainable operations brings the book up to date with recent developments, showing how operations impact social, ethical, and environmental issues. Increased emphasis on risk in operations strategy and the importance of external and internal context. Updated with several new exa